Discourses of Gender and Political Violence in South Africa. (7th April 2021) - Cornell, Josephine; Malherbe, Nick; Seedat, Mohamed; Suffla, Shahnaaz
Abstract: Politically violent women are regularly muted or made exceptional. Yet, underplaying women's involvement in political violence obscures the systemic nature of such violence. We employ a discursive psychology analysis of an in-depth interview with a South African woman who has been involved in decades of political activism, and identified two discourses: Gendering Politically Violent Symbols and Enactments, where political violence was wielded as a symbol, and Gendering Political Organizing, wherein feminist agencies were directed against political structures. Together, these discourses indicate how gender identity is simultaneously consistent and at odds with political identity and how gender intersects with political violence.